Evaluation of soybean (Glycine max) and pigeonpea (Cajanus cajan) lines for advantage in intercropping systems - JAGTAP, J G; HOLKAR, S (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1991-93 to evaluate 4 genotypes of pigeon pea [Cajanus cajan (L.)Millsp.] and 2 genotypes of soybean [Glycine max'(l.) Merr.] in soybean-based intercropping system to study theadvantage of intercropping. The results interpreted indicating that the various lines of pigeonpea selected from thepromising genotype 'ICPL 87' showed a Ya1;able response with soybean genotypes in intercropping. The intercroppingof soybean-pigeonpea genotypes gave land-equivalent ratio of 1.26-1.36. Only 5 out of 8 intercropping treatments ofsoybean and pigeonpea genotypes gave an economic advantage of 1 (monetary equivalent ratio 1.01) to 11 % (monetaryequivalent ratio 1.11) compared with the most economic sole crop in respect to grain yield. The disparity betweenthe values of land-equivalent ratio and monetary equivalent ratio indicates that substantial agronomic advantage doesnot guarantee an economic advantage in intercropping.